Characterization of fused deposition modelling printed kenaf fibre reinforced poly-lactic acid composites - Jamadi, Aida Haryati (2023)
Natural fibre as a reinforcing agent has been widely used in many industrial applications. However, the reinforcing agent devotes a better strength when embedded with a polymer matrix. Nevertheless, the characteristic of natural fibre and polymer matrix are in contrast, as natural fibre is hydrophilic, while polymer is hydrophobic in nature. Natural fibre is highly hydrophilic due to the presence of a hydroxyl group (-OH), while polymer matrix has an inherent hydrophobic characteristic which repels water. This issue has been fixed by modifying the natural fibre’s surface using a chemical treatment combining an alkaline treatment and a silane coupling agent. This modifying process of natural fibre might reduce the attraction of water and moisture content and increase natural fibre surface roughness, which improves the interfacial bonding between these two phases. Fused Deposition Modelling (FDM) gets the most attention in development and manufacturing industries. The demand for FDM in industries increases gradually over time and attracts many researchers to enhance the quality of the FDM’s fillers. To overcome the issue and replace the current fibres and achieve the bio-composites fibre, researchers suggested using natural fibre to replace the synthetic and carbon fibres as the reinforcement, which is also combined with bio-polymer matrix such as thermoplastics as the polymer matrix in FDM’s industries. The effect of alkaline and silane treatment has been proven by performing the mechanical test, 1.0% silane treatment displayed better strength performance (57.846MPa) and tensile modulus (1.174GPa) as compared to other composites, which was proven by performing Scanning Electron Micrograph (SEM). The composites properties have been obtained by performing Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA) and capillary rheological tests. By claiming 1.0% as the optimum silane concentration that perform better in mechanical properties, several factors need to be considered such as size and dimensional of fibre in binding. This factor has been studied by variying the size of natural fibre as the responding variables with a fix weight percentage of fillers. This modifying process of natural fibre might increase the dispersion of filler towards polymer matrix and increase the internal strength of composites, subsequently improving the interfacial bonding between these two phases. As the results tensile test indicateds that ≤100μm have hisghest strength (45.578MPa) with highest tensile modulus (1.096GPa) which also has been proven under SEM. The surface quality has been visualize by using 3D profilometer As a conclusion, by reducing the size of fillers, kenaf fibre composites could develop high strength performance in industry applications.